OPTICAL DEVICES IN DENTISTRY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In the course of professional dental practice, the visual system is subjected to considerable strain, while an ergonomically unfavorable working posture represents an additional risk factor. The establishment of ergonomic working conditions involves the development of effective teamwork skills, including the active involvement of an assistant, as well as the use of optical magnification systems of various types. Four-handed dentistry combined with high-quality visual enhancement provides significant advantages for dental professionals. In particular, occupational risk factors such as forced posture, muscular tension, and spinal overload are reduced. Visual fatigue is minimized, while the accuracy of clinical procedures, diagnostic reliability, and overall treatment quality are significantly improved.
Keywords: Optical devices, magnification, dentistry, ergonomics.